Water demand management: potential and pitfalls. Background paper - Molle, Francois (International Development Research Centre, 2010)
Water Demand management has received much emphasis from development agencies in the last decade. The concept stemmed from a growing awareness of the externalities of large scale water resources development and of an assumed state of wastage in the use of water by many sectors, notably agriculture. The paper examines critically the scope of the three main water demand management objectives: saving water in water short basins; reducing irrigation demand through pricing; and reallocating water to higher value uses. It argues that the gains that can be achieved through demand management are often overestimated. Because of the closing/closed nature of water short basins, most water-saving interventions result in spatial shifts of water use rather than savings. Water pricing is often proposed as a way to curb water use but its introduction in irrigated agriculture is shown to be problematic. The economic argument for re-allocation to higher value uses is also critically reviewed. Despite the limitations faced by water demand management policies (and the importance of being aware of them), these policies must be pursued -with a full understanding of their implications and limitations- because they are both needed and, sometimes, the only options at hand.